A single region of the Phytophthora infestans avirulence effector Avr3b functions in both cell death induction and plant immunity suppression. (25th January 2023) - Gu, Biao; Gao, Wenxin; Liu, Zeqi; Shao, Guangda; Peng, Qin; Mu, Yinyu; Wang, Qinhu; Zhao, Hua; Miao, Jianqiang; Liu, Xili
Abstract: As a destructive plant pathogen, Phytophthora infestans secretes diverse host‐entering RxLR effectors to facilitate infection. One critical RxLR effector, PiAvr3b, not only induces effector‐triggered immunity (ETI), which is associated with the potato resistance protein StR3b, but also suppresses pathogen‐associated molecular pattern (PAMP)‐triggered immunity (PTI). To date, the molecular basis underlying such dual activities remains unknown. Based on phylogenetic analysis of global P. infestans isolates, we found two PiAvr3b isoforms that differ by three amino acids. Despite this sequence variation, the two isoforms retain the same properties in activating the StR3b‐mediated hypersensitive response (HR) and inhibiting necrosis induced by three PAMPs (PiNpp, PiINF1, and PsXeg1) and an RxLR effector (Pi10232). Using a combined mutagenesis approach, we found that the dual activities of PiAvr3b were tightly linked and determined by 88 amino acids at the C‐terminus. We further determined that either the W60 or the E134 residue of PiAvr3b was essential for triggering StR3b‐associated HR and inhibiting PiNpp‐ and Pi10232‐associated necrosis, while the S99 residue partially contributed to PTI suppression. Additionally, nuclear localization of PiAvr3b was required to stimulate HR and suppress PTI, but not to inhibit Pi10232‐associated cell death. Our study revealed that PiAvr3b suppresses the plant immune response at different subcellular locations and provides an example in which a single amino acid of an RxLR effector links ETI induction and cell death suppression. Abstract : Phytophthora infestans RxLR effector Avr3b activates effector‐triggered immunity and suppresses pathogen‐associated molecular pattern‐triggered immunity in the nucleus, while nuclear localization of Avr3b is not required for inhibition of effector‐induced cell death.